Boron fertilization improves seed yield and harvest index of Camelina sativa L. by affecting source-sink. (14th October 2016) - Khan, Shahbaz; Rehman, Hafeez ur; Wahid, Muhammad Ashfaq; Saleem, Muhammad Farrukh; Akhtar Cheema, Mumtaz; Basra, Shahzad Maqsood Ahmed; Nadeem, Muhammad
ABSTRACT: The impact of soil (1, 2 kg ha −1 ) and foliar (100, 200 mg L −1 ) boron (B) with control (no B) was evaluated on phenology and yield formation of Camelina each applied at stem elongation and flowering stages. Foliar (200 mg L −1 ) or soil B (2 kg ha −1 ) resulted in earlier flowering and maturity, increased fruit bearing branches (19.68%), number of siliqua, seeds per siliqua (4.6%), biological yield (15%), seed yield (24%), harvest index (11.4%) and oil contents (23%) than no B. Increased fruit bearing branches, seed filled siliqua or seed numbers, harvest index and oil quality can be attributed to changes in dry matter accumulated of stem with simultaneous increase in siliqua dry weight with foliar or soil applied B. In crux, foliar (200 mg L −1 ) or soil applied (2 kg ha −1 ) B seems promising to improve seed and oil yield, harvest index of Camelina sativa under B deficient condition.